Gestão de dados de pesquisa nas bibliotecas universitárias públicas paulistas - Rosa, Ana Beatriz Almagro Rodrigues (Universidade Federal de São Carlos, 2021)
In E-Science context, diverse and varied research data are developed and generated in a collaborative way. These data can be shared with other researches, improving scientific development, publishing quality research and new scientific discoveries. However, as they are generated in a short period, with few conditions to be analyzed and identified, there is a risk of these data being lost due to poor preservation. Thus, research funding agencies begin to require a Data Management Plan document to researches, with the submission of their research projects. The academic libraries are part of this process as they help researchers provide Research Data Management services. Therefore, the goal of this research was to question and identify how the public academic libraries of the state of São Paulo are inserted in the process of research data management. The methodology used to accomplish this goals was a theoretical survey of the literature related to the Information Science; communication and scientific paradigms; Open Science, that allowed the identification of a direct interference of this theme in scientific practices, increased production of research data and the consequent need to manage and preserve them. From the perspective of the selected literature, an investigation and survey of research data management practices were made in the public academic libraries of the state of São Paulo identified in the FAPESP research data metasearch.
Research data management in public university libraries in São Paulo
Keywords: Dados de pesquisa; Gestão de dados de pesquisa; Bibliotecas universitárias; Plano de gestão de dados; Ciência aberta; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO